The Effect of Encapsulator Machine Speed ​​on Composite Microcapsule Size - Insyira, Athalla Rania; Athari, Hafizha Nur; Sukardi, Purnama; Wijaya, Rudy (PT. Artha GenetikaLab Indonesia, 2024)
Microcapsules are small round particles with uniform walls or layers around them that generally have a diameter from 0.2 to 5000 µm. Microencapsulation is a process that converts solid or liquid materials into capsule form which aims to protect and maintain active ingredients from environmental influences such as humidity, high temperature, light exposure, or oxidation processes. Microcapsule formation can be done using the crosslink method. Microcapsule size is affected by the stirring speed of the encapsulator machine. During microencapsulation of fish meal with eggs and gelatin using the crosslink method, the stirring speed is 3000 rpm, 3500 rpm, 4000 rpm, 4500 rpm, and 5000 rpm. In the microencapsulation process of fish meal with eggs and gelatin, the smallest average diameter at a speed of 5000 rpm, which is 18.220 ± 3.3 µm and has a yield of 26% while the largest diameter at a speed of 3000 rpm, which is 33.53 ± 4.8 µm and has a yield of 28.4%. Based on the results of the Tukey SPSS test, the speeds of 3000 rpm (33.53 ± 4.8 µm), 3500 rpm (30.25 ± 4.4 µm), 4000 rpm (26.30 ± 3.5 µm), 4500 rpm (22.50 ± 4.1 µm), and 5000 rpm (18.220 ± 3.3 µm) were very significantly different (P <0.05) in each treatment.